2008
DOI: 10.1016/j.physio.2007.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating writing for publication

Abstract: In order to develop physiotherapy practice and interventions, it is essential that both service development and research be brought into the public domain. Writing for publication requires a high level of writing skills, and clinicians facing competing demands for their time need strategies for productive writing. These skills and strategies are not always developed in undergraduate or postgraduate courses. This study assessed a writing for publication course for allied health professionals. It explored the wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 11 publications
(14 reference statements)
0
42
0
1
Order By: Relevance
“…The importance of this finding is that it more reliably establishes the lack of an evidence base for effective training methods to ensure the scientific quality of research output. For example, previous research on authors of scientific manuscripts suggests that despite promotion and tenure being closely linked to their research and publication portfolio, most of them have no formal training in writing for publication and that they developed their skills mainly through a process of trial and error [37]. Similarly, most clinicians also receive little [38] to no [37] formal training in writing for publication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of this finding is that it more reliably establishes the lack of an evidence base for effective training methods to ensure the scientific quality of research output. For example, previous research on authors of scientific manuscripts suggests that despite promotion and tenure being closely linked to their research and publication portfolio, most of them have no formal training in writing for publication and that they developed their skills mainly through a process of trial and error [37]. Similarly, most clinicians also receive little [38] to no [37] formal training in writing for publication.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous research on authors of scientific manuscripts suggests that despite promotion and tenure being closely linked to their research and publication portfolio, most of them have no formal training in writing for publication and that they developed their skills mainly through a process of trial and error [37]. Similarly, most clinicians also receive little [38] to no [37] formal training in writing for publication. Additionally, most incidences of misconduct [39e42] have been found to stem from negligence, poorly performed science, investigator bias, or lack of knowledge, rather than acts of fraud [43], suggesting a need for better training.…”
Section: Discussionmentioning
confidence: 99%
“…groups where the members are concentrating on producing academic writing, have been found successful for both professionals (Lee and Boud 2003, Morss and Murray 2001, Murray and MacKay 1998, Murray and Newton 2008and Washburn 2008), and at the PhD level (Aitchison 2003, Aitchison and Lee 2006, Chihota 2008and Grant 2006. If such groups have had such success for other academic writers, it stands to reason that they may benefit lessexperienced master's level writers as well.…”
Section: Background: Writers' Groups For Academic Writersmentioning
confidence: 99%
“…The reasons for the increase in the number of publishing authors remain unclear, but various initiatives have been identified as influencing participation, such as full-time or parttime faculty appointment [15,16], academic progression [14], and involvement in writing groups [17,18]. There does, however, appear to be a persistent problem with maintaining practitioner engagement in research and scholarship, with over three-quarters of authors contributing only a single article to any of the four journals over the eight-year period.…”
Section: Discussionmentioning
confidence: 99%